PENGARUH LINGKUNGAN BELAJAR TERHADAP PRESTASI AKADEMIK SISWA - Ferina Swesty Wulandari; Shinta Lathifatul Humayra; Ikmawati, Ikmawati; Zainuddin Untu (CV. ADIBA ASIHA AMIRA, 2025)
Academic achievement is the first aspect observed in students, as it reflects the results of the learning process they have undergone while acquiring knowledge at school or college. One of the factors that can affect students academic achievement in school is the environment. The environment provides influence and input to children in the form of support and challenges, while the brain’s nervous system plays a role in processing these influences effectively, enabling students to investigate, assess, analyze, and find solutions to the problems they face. This article employs a literature study research method, where thedata used does not come from direct field research but rather from various academic sources such as reference books, scientific journals, research articles, and previously published study reports.